Analisis Strategi Kampanye Iklan Online Dalam Meningkatkan Brand Awareness Pada VR Journey Indonesia Senayan Park - Arinal Razaq Al Haq; Sugeng Widodo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to analyze the online advertising campaign strategy implemented by VR Journey Indonesia in an effort to increase brand awareness. In today's digital era, marketing through social media and other digital platforms is the main strategy in reaching consumers more widely and efficiently. VR Journey Indonesia utilizes virtual reality technology to convey educational stories based on immersive experiences, supported by intensive digital campaigns.The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. Data analysis was carried out using the SWOT approach to identify strengths, weaknesses, opportunities, and threats in the digital marketing strategy being implemented.The results of the study show that the online advertising campaign carried out by VR Journey Indonesia has strengths in educational and innovative technology-based content, as well as attractive promotional strategies through social media. However, there are challenges in terms of technology education to consumers who are not yet familiar with digital marketing. With the right strategy, digital marketing has proven effective in increasing brand awareness and strengthening VR Journey Indonesia's position in the educational digital market Keywords: Online Advertising Campaign, Brand Awareness, Digital Marketing, VR Journey, SWOT.